Equitable gender relations are at the heart of food and nutrition security - Zaremba, H. (2024)
Although they bear more responsibility for their families' food and nutrition security, women are more likely to go hungry than men, globally. Underlying social inequalities undermine household food and nutrition security, but we know that women's empowerment-not just an honorable goal itself-can boost food security and overall health. Working with men and masculinities is another step along the path to achieving nutrition SDGs, using gender· transformative approaches; coordinated, multistakeholder approaches at multiple levels; robust policies-all informed by excellent data.